Long‐term therapeutic effectiveness of maintenance enteral nutrition for Crohn's disease. Issue 2 (16th January 2015) - Konno, Mutsuko; Takahashi, Michiko; Toita, Nariaki; Fujiwara, Shin‐ichi; Nojima, Masanori
Abstract Background Long‐term effectiveness of enteral nutrition for maintaining remission in pediatric Crohn's disease (CD) is poorly documented. The aim of this study was therefore to examine the long‐term effectiveness of enteral nutrition with aminosalicylates as maintenance therapy for those in whom remission was primarily induced by total parenteral nutrition or exclusive enteral nutrition with aminosalicylates. Methods We retrospectively analyzed data for 58 pediatric patients with newly diagnosed CD during a median follow‐up period of 50 months (range, 12–216 months). Data for remission‐induced patients in whom enteral nutrition with aminosalicylates was used as maintenance therapy were analyzed with particular reference to time to first relapse and time to first intestinal surgery. Results Twenty‐five (43.1%) of the patients relapsed with a median duration of remission of 32.4 months (range, 6–73.2 months). The cumulative rates of continuous remission were 0.88 (95%CI: 0.79–0.96) at 1 year, 0.73 (95%CI: 0.61–0.85) at 2 years, and 0.52 (95%CI: 0.35–0.68) at 5 years. None of the patients received corticosteroids, immunomodulators or anti‐tumor necrosis factor agents until relapse. Disease location had no impact on timing of relapse, but with regard to disease behavior there was a trend towards earlier relapse in patients with penetrating type. Only six of the 58 patients (10.3%) needed intestinal surgery. There was a trend towards need for surgery in patients with ileal disease and with stricturing type. Conclusions Enteral nutrition therapy with aminosalicylates is effective for maintaining remission and decreasing the rate of intestinal surgery in pediatric CD.